2018
DOI: 10.1177/2058460118817918
|View full text |Cite
|
Sign up to set email alerts
|

Extensive perivascular dissemination of cerebral miliary tuberculomas: a case report and review of the literature

Abstract: Cerebral tuberculosis (TB) presents most frequently as meningitis in the basilar cistern; however, it can also manifest in various other ways, such as localized encephalitis, abscess, and tuberculoma. Here, focusing on imaging findings, we report an immunocompetent case who demonstrated multiple parenchymal lesions and was diagnosed with cerebral TB after testing positive on QuantiFERON (QTF); her clinical signs/symptoms and laboratory findings responded well to anti-TB medication therapy. The patient was a 60… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Delayed diagnosis in miliary TB patients can cause serious complications including cranial nerve involvement, convulsions and death [ 16 ] as a seizure occurred in our case. Machida et al’s report showed 1% of TB patients had CNS involvement which is about a high mortality rate and permanent neurological sequelae [ 33 ]. Fortunately, in the present case, follow-up interventions showed no neurological sequelae and she was in good general condition.…”
Section: Discussionmentioning
confidence: 99%
“…Delayed diagnosis in miliary TB patients can cause serious complications including cranial nerve involvement, convulsions and death [ 16 ] as a seizure occurred in our case. Machida et al’s report showed 1% of TB patients had CNS involvement which is about a high mortality rate and permanent neurological sequelae [ 33 ]. Fortunately, in the present case, follow-up interventions showed no neurological sequelae and she was in good general condition.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, intraparenchymal tuberculomas TB often appears in the frontal and parietal lobes; however, the infratentorial region is more commonly affected in children [7] . The imaging findings of brain miliary tuberculomas on MRI include tuberculosis that are often smaller than 2.5 cm in diameter, hypointense lesions on T1-weighted image (T1W), hypo- or hyperintense lesions on T2-weighted image (T2W), with a central hypointensity on T2W and homogeneous enhancement in the initial stage and ring enhancement in the late stage [7] . In our case, MRI showed diffuse miliary lesions smaller than 2 mm in diameter, with homogeneous enhancement in the cerebral parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Machida et al, 2018 [16] Brain A patient diagnosed with tuberculous meningitis and multiple periventricular tuberculomas. One month after initiation of anti-TB therapy, tuberculomas increased in number and size.…”
Section: Site Of Paradoxical Reaction Conclusion and Manifestationsmentioning
confidence: 99%